NANOSTRUCTURED AND DISORDERED OXIDES OF MANGANESE OBTAINED BY ELECTROCHEMICAL DOPING TECHNIQUE - Sokolsky, George V.; Ivanova, Natalya D.; Ivanov, Sergey V.; Boldyrev, Eugene I.; Rubtsova, Nina D.; Kobulynskaya, Olga V. (Proceedings of National Aviation University (archive), 2008)
Disordered and semi-amorphous oxides of manganese have been prepared by the anode electrodeposition from fluoride containing electrolytes of manganese sulfate at the presence of additives of cobalt(II), copper(II), lithium ions. Materials obtained were characterized with XRD, TGA, TEM, Fourier spectroscopy. The low doping by ions of cobalt, copper, and lithium have also been studied. It has been shown that the latter additives allow varying the phase composition, defects concentration and size of crystallites of the anode product. The heavier doping leads to the formation of X-ray amorphous products.